First record of the genus Thetispelecaris Gutu & Illife, 1998 (Crustacea: Peracarida: Bochusacea) from a submarine cave in the Pacific Oceannaruse@lab.u-ryukyu.ac.jp - Shimomura, Michitaka; Fujita, Yoshihisa; Naruse, Tohru (Zootaxa, 2012)
A new species of Thetispelecaris is described from a submarine cave in Japan as the first record of the genus from thePacific Ocean. Thetispelecaris kumejimensis n. sp. differs from its congeners in the following combination of characters:carapace 1.1 times as long as wide; antennal scale with 3–4 setae; maxilliped dactylus with 4 slender setae; basis of pere-opod 1 with 2 long setae ventrodistally; exopod of pereopods 4 and 5 4-segmented; basis and ischium of pereopod 3 sep-arated; basis and ischium of pereopods 4–6 partly fused; and pleopods 4 and 5 with 2 setae apically. This study represents the sixth species of the order Bochusacea.